Language as a communication resource and its place in the representation of world practices: philosophical and linguistic approach - Vysotki, Vadim Mikhailovich; Patalashko, Ekaterina Viktorovna; Stepanenko, Victoria Evgenievna; Makarova, Tatiana Valerievna; Balabanova, Iuliia Andreevna (Linguistics and Culture Review, 2021)
The paper considers language as a communication resource and its place in the representation of world practices is evaluated from the standpoint of a philosophical and linguistic approach. The authors note that discussions of language are necessarily based on ontological, sometimes contradictory ideas about languages or language use. These reports are not limited to categories that attempt to describe and analyze them. Moving forward, there are still opportunities for more interaction with language ontologies. Thinking in the ontological register is not an interpretation or description, but rather, much more importantly, it is the identification and display of hypotheses hidden in the world of language. Researchers insist on assigning ontological significance to various practices and regulations. This requires moving away from ideological analysis and the assumption that they represent multiple points of view that illuminate various partial aspects of an independently existing and ultimately determined phenomenon, and towards an approach that aims to purify reality - worlds - as created through practices. It can be stated that specific ways of perceiving a language are more complex and, therefore, more comprehensive descriptions of languages. It is inevitable that contradictory ideas about language can coexist.